The Effect of CARTRACK Application on Heavy Equipment Productivity Monitoring at IKN 3A Toll Project - Ramadhan Okta Valencia; Ary Setyawan; Fajar Sri Handayani (Indonesian Journal Publisher, 2025)
This study aims to analyze the effect of the CARTRACK application on the productivity and operational efficiency of heavy equipment in the IKN 3A Toll Road Project, Karangjoang–KKT Kariangau segment. CARTRACK is a GPS-based telematics system that records real-time data on equipment operation, including effective working hours, idle time, and work volume. A comparative quantitative method was used by evaluating data obtained from two monitoring methods: manual recording using Daily Time Sheets and digital tracking through CARTRACK. Six types of heavy equipment were observed: Excavator, Dump Truck, Truck Mixer, Truck Trailer, Vibratory Soil Compactor, and Crane. Data were processed using productivity and efficiency formulas and analyzed using linear regression. The results indicate that the use of CARTRACK significantly improves both productivity and efficiency. The Dump Truck showed an increase in productivity from 2.05 m³/hour to 2.98 m³/hour, while the Crane recorded the highest efficiency gain at 41%. Regression analysis demonstrated a strong positive relationship between effective working hours and productivity, with the highest coefficient of determination (R² = 0.5895) and correlation coefficient (R = 0.7678) for the Dump Truck. These findings confirm that CARTRACK enhances monitoring accuracy and contributes to more efficient and productive heavy equipment operations in large-scale infrastructure projects